Resistance Heated Catalytic Converter (RHCC) with copper oxide catalyst for reducing HC/CO emission from automobile. (2021) - Bhaskar, K; Sassykova, L.R.; Prabhahar, M.; Percis, E. Sheeba; Nalini, A.; Jenish, T.; Jayarajan, J.; Jayabalakrishnan, D.; Sendilvelan, S.; Krishnamoorthi, Sangeetha
Abstract: Rigorous enforcement of emission norms requires a control over cold/cool start emissions on a present-day automobile with catalytic converter. After the car warms up, these converters are really capable in controlling HC and CO emissions. The catalyst isn't efficient during warm-up or cool start period because of its low operating temperature. Emission reduction is actually possible by heating the catalyst and changing the substrate of the catalyst used in car. In this work, with the help of band type resistance heaters are used to heat the metal oxide catalyst placed in Resistance Heated Catalytic Converter (RHCC) which will help the conventional converter. It is attempted to study the emission from multi-cylinder SI automotive engine, by developing better catalysts. Form the experimental investigation, it's observed that RHCC with copper oxide catalyst when utilized with the conventional catalytic converter (CCC), the CO and HC emissions are significantly reduced. It can be seen that in twelve seconds after cool start the value of CO% by volume is 4.3 and significant reduction of 0.7% of CO at 180 s is observed for RHCC-PC configuration with 90 lpm air supply for duration of forty seconds. It can be seen that in 120 s after cool start the value of HC in ppm is 315 in contrast with baseline readings. The maximum reduction is actually achieved when the RHCC with copper oxide catalyst and 90 lpm of air supply for forty seconds duration from the cool start of the engine.